Digital fundamentals - Floyd, Thomas L. (Pearson Prentice Hall, 2015)
""Digital Fundamentals: A Systems Approach"" offers unique coverage of digital technology with a system emphasis, providing a fundamental grounding in the basic concepts of digital technology and systems reinforced by an abundance of illustrations, examples, applications, and exercises